Computation modeling of laminated crack glass windshields subjected to headform impact. (December 2017) - Yu, Guizhen; Zheng, Yanting; Feng, Bill; Liu, Binghe; Meng, Kangpei; Yang, Xianfeng; Chen, Hongshun; Xu, Jun
Abstract: Polyvinyl butyral-laminated glass has been extensively applied to automotive windshields to reduce the severity of head injuries resulting from pedestrian–vehicle crashes. Thus, designing an optimized pedestrian protection design for laminated windshields (LWs) has become a priority. In this study, finite element models that describe LWs, headform, and sub-frontend vehicles are established to numerically investigate the dynamic mechanical behavior of LWs subjected to headform impact. First, headform impact tests are conducted on five different locations on an LW. Second, a single-layered model for LW is proposed using a formatted material constitutive description. A reasonable consistency is observed between the numerical simulation and test results for the acceleration–time behavior of LWs. Third, a triple-layered LW model is devised to provide a highly realistic cracking morphology with an enhanced impact response for LWs. Fourth, the characterized material constitutive properties are applied to LWs with different thicknesses on another vehicle. The simulation and test results show a satisfactory correlation, thereby providing a solid foundation for formulating pedestrian protection design guidelines for LWs to reduce the severity of head injuries resulting from pedestrian–vehicle crashes.